EFFECTIVENESS OF DECOCTION WATER OF BAY LEAF (Syzygium polyanthum) FOR HEALING OF PATHOLOGICAL VAGINAL DISCHARGE - Syastriani Isna Putri Syarif; Wa Ode Sitti Justin (Journal of Vocational Health Studies, 2026)
Background: Vaginal discharge or fluor albus is a disorder of the reproductive tract, particularly affecting the vaginal area. Pathological vaginal discharge requires prompt treatment because its complications may include ovarian infection and may eventually lead to infertility. Based on the above, researchers seek to conduct research to overcome pathological fluor albus by utilizing natural ingredients that are believed to be easily obtained in the community, specifically bay leaves (Syzygium polyanthum) which are mixed into traditional ingredients. Purpose: This study aims to determine the effectiveness of bay leaf decoction for the healing of pathological fluor albus. Method: This study used a quasi-experimental design with a one-group pretest–posttest approach. The sample included 56 respondents. Data were analyzed using a Paired T-test. A pretest was carried out before the intervention, followed by a demonstration of how to prepare the bay leaf decoction. For seven days, respondents were monitored twice a day and asked to complete a checklist as evidence that they had performed the rinsing, then submit a photo of the checklist via whatsapp. After the seven-day intervention period, a home visit was conducted to administer the posttest. Result: The results showed a significant difference between the pretest and posttest scores (Z = -4.895; p-value = 0.000), with 30 respondents experiencing a reduction in symptoms. The intervention proved effective in reducing pathological vaginal discharge. Conclusion: Bay leaf decoction is effective in alleviating symptoms of pathological vaginal discharge, making it a promising herbal alternative for managing cases of pathological vaginal discharge.